Apoptosis pathway of Gelam (Melaleuca cajupati) honey on human colorectal carcinoma (HCT116) / Dr. Wan Iryani Wan Ismail and Dr. Mizaton Hazizul Hassan - Wan Ismail, Wan Iryani; Hazizul Hassan, Mizaton (Research Management Institute (RMI), 2013)
Honey has been used for medical purposes since a long time ago. It had antimicrobial, antiviral and antiparasitic activities, and showed anti-inflammatory, antioxidant and antimutagenic effects. Previous studies demonstrated that honey may have potential as an anticancer agent as well. However, study of honey as anticancer agent is still at infancy level particularly in Malaysia. Several type of Malaysian honey such as Gelam, Pineapple and Coconut honey may have potential as an anticancer agent. Gelam honey showed better antimicrobial, antioxidant and wound healing activities, and therapeutic value than other honey and natural products. This was due to the difference in their phenolic contents which has a direct correlation to the antioxidant activity of honey. Antioxidant activity prevents oxidation reactions of free radical such as hydroxyl radical in cancer cell lines. High activity of antioxidant may provide a better anticancer agent. Thus, the honey will be chosen for the first time to analyse the possible mechanism pathway, in particular apoptosis pathway of human breast cancer (MCF7) using Western blot analysis. Understanding the molecular basis of Gelam honey to act against the cancer cell lines may shed new light on these honeys as a new anticancer agent in the future.